Mathematical model of growth of two purelines of Padjadjaran female quail aged 0 to 6 weeks - Anang, A.; Indrijani, H.; Sujana, E. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
A research was conducted at Quail Breeding Centre of Padjadjaran University.  A hundred quails of female black and brown color of each line was observed from hatch to age of six weeks. Four growth models were compared: Gompertz, Logistic, Richards, and MMF. The best fit was measured with Coefficient of determination (R2) and standard error of prediction (se). The results showed that all observed models have high accuracy with R2 ranging from 0.9950 to 0.9988 for black color, and 0.9984 to 0.9992 for brown color respectively. Standard errors of prediction (SE) ranged from 1.99 g to 4.01 g for black, and from 1.92 g to 2.52 g for brown, respectively. Gompertz model was more favorable with R2 and SE of 0.9988 and 1.99 g for black, and 0.9991 and 1.92 g for brown, respectively. Age at inflection, maximum average daily gains and weights at inflection were 4.18 week, 27.87 g and 100.23 g for black line and 3.38 week, 25.05 g and 75.34 g for brown line, respectively.